The retreat of democracy and other itinerant essays on globalization, economics, and India - Basu, Kaushik (Ranikhet : Permanent Black : Distributed by Orient Longman, 2007)
Collection of author's excerpts from different journals focussing on economic and polical globalization with special reference to India.
"For sale only in South Asia"--Verso of t.p.
Includes bibliographical references and index.
Keywords: Globalization -- Economic aspects -- India; Globalization -- Political aspects -- India; Globalization -- Economic aspects; Globalization -- Political aspects; India -- Economic policy -- 1991-